Skill-biased technological change and skill-enhancing trade in Turkey: Evidence from longitudinal microdata - Ilina Srour; Erol Taymaz; Marco Vivarelli (Institute for the Study of Labor (IZA), 2013)
This paper explores the causes of skill-based employment differentials within the Turkish manufacturing sector over the period 1980-2001. Turkey is taken as an example of a developing economy that, in that period, had been technologically advancing and becoming increasingly integrated with the world market. The empirical analysis is performed at firm level within a dynamic framework using a two-equation model that depicts the employment trends for skilled and unskilled workers separately. In particular, the System Generalized Method of Moments (GMM-SYS) procedure is applied to a panel dataset comprised of 17,462 firms. Our results confirm the theoretical expectation that developing countries face the phenomena of skill-biased technological change and skill-enhancing technology import, both leading to increasing the employment gap between skilled and unskilled workers. In particular, strong evidence of a relative skill bias emerges: both domestic and imported technologies increase the demand for skilled labor 5 to 6 times more than the corresponding demand for the unskilled labor. Finally, learning by export also appears to have a skill biased impact, but to a lesser extent.
Keywords: F16; O33; 330; skill-biased technological change; technology transfer; panel data; GMM-SYS